n+N+1N+2=72

Simple and best practice solution for n+N+1N+2=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+N+1N+2=72 equation:


Simplifying
n + N + 1N + 2 = 72

Reorder the terms:
2 + N + 1N + n = 72

Combine like terms: N + 1N = 2N
2 + 2N + n = 72

Solving
2 + 2N + n = 72

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 2N + -2 + n = 72 + -2

Reorder the terms:
2 + -2 + 2N + n = 72 + -2

Combine like terms: 2 + -2 = 0
0 + 2N + n = 72 + -2
2N + n = 72 + -2

Combine like terms: 72 + -2 = 70
2N + n = 70

Add '-1n' to each side of the equation.
2N + n + -1n = 70 + -1n

Combine like terms: n + -1n = 0
2N + 0 = 70 + -1n
2N = 70 + -1n

Divide each side by '2'.
N = 35 + -0.5n

Simplifying
N = 35 + -0.5n

See similar equations:

| x+6+2x+4+x-6=180 | | 1.25c+2a=339 | | (x+5)(x-6)(4x-5)=0 | | 5.83x+34.98=69.96 | | 2(4x-3)+9=51 | | 1.25c+2.00a=339.00 | | F(x)=-16x^2+1776 | | 400/1210 | | 3x-5+76=180 | | 3x-6=-3x-2 | | X/12-172003 | | 4(3y+1)=8 | | z/2-7i | | 6(6+q)(4-q)=0 | | 3x^6-2x^3-8=0 | | 15=-3+6x | | 2x-1/x-2=1 | | t^2+8t+48=0 | | 10x(x+7)=180 | | 5x^2=8-2 | | 157+-11x=60 | | 2(9x+8)=3(6x-2) | | 13=2c+5c+3 | | (2x-3)=7 | | 2(19)-3=(19)+16 | | 100+15m=y | | -12=6+9x | | 78/60=51/x | | b=5d*4 | | 290/2000 | | 3(2x-1)=5(1-2x) | | b=5*4d |

Equations solver categories